How Stress Influences The Physiological Functions Of The Human Body: A Bibliometric Mapping 2019-2024 - Saminan, Saminan; Linda Julisafrida; Saminan, Nurul Fajri; Muhammad Khairul (Jurnal EduHealth, 2024)
Stress is an important component of modern life and has been widely recognized as a factor that negatively impacts health. The aim of this research is to map the influence of stress on the physiological functions of the human body over the last five years (2019–2024) using data from the Scopus database. Bibliometric analysis was conducted with VOSviewer visualization to depict publication patterns, citations, keywords, and relation-ships between concepts. The results indicate that the United States was the country with the highest number of publications in 2019, with 110 documents. Overall, the keywords "stress", "physiology", and "body" were the most frequently used. However, the topic of "hyper-thermia", a condition where the body temperature is higher than normal, has not been extensively re-searched. This study highlights the importance of un-derstanding in greater detail the mechanisms of the body's response to stress and identifying areas that re-quire further investigation, such as hyperthermia, to ef-fectively address the impact of stress on health.